Corporate real estate management during the transition in Russia - Richard Grover; Mikhail Soloviev; Vladimir Zakharchenko (Journal for East European Management Studies, 2007)
The article reviews corporate real estate management problems during the transitional period of the Russian society between 1991 and the present time. There are interconnected processes of forming and developing the market legislative base for a real estate market, corporative structures, and real estate management. It illustrates the strategic and operational interaction between the corporation management system and its real estate subsystem, and the functions of the corporate real estate department and managers in the top management of corporations, showing the importance of good quality information about real estate assets. Imbalance between the three results in serious problems and these have been a feature of the corporative development during this period. – – Der Artikel berichtet über die Probleme bei der Immobilienverwaltung von Firmen in Russland von 1991 bis heute. Es gibt Zusammenhänge zwischen der sich entwickelnden Gesetzgebung für den Immobilienmarkt, den gesellschaftlichen Strukturen und dem Immobilienmanagement. Der Artikel erklärt die strategischen und operativen Interaktionen zwischen dem Management-System der Firmen, ihrem Immobilienmanagement-Teilsystem, den Funktionen der Immobilienabteilung und den Managern der Unternehmensleitung und zeigt die Wichtigkeit von qualitativ hochwertigen Informationen über den Immobilienbesitz. Ein Ungleichgewicht zwischen der Entwicklung der Gesetzgebung, den Unternehmensstrukturen und dem Immobilienmanagement führt zu ernsthaften Problemen, welche eine Besonderheit für die Firmenentwicklung in Russland während dieser Periode waren.
Keywords: 650; transition period; corporate development; legislative base; real estate management